Response and prognosis to neoadjuvant chemotherapy in women early breast cancer of HER2-low status - Li, Yongtao; Buerliesi, Tangnuer; Xu, Wenting; Yi, Lina; Wuwalihan, Fulati (Frontiers in Oncology, 2025)
ObjectiveWith the significant clinical benefits of antibody-coupled drugs (ADCs) against HER2, the HER2-low-expressing population has come into focus. HER2-low-expressing patients express this membrane protein despite the absence of HER-2 amplification. Whether there is a difference in outcome and prognosis between patients with HER2-low expression and those with HER2–0 expression has not yet been clarified, and more clinical data are needed to characterize them.MethodsClinical and pathological data of HER2-low versus HER2-0-expressing breast cancer patients treated with neoadjuvant chemotherapy (NACT) and operated at Xinjiang Uygur Autonomous Region Cancer Center from 2015 to 2018 were reviewed, and the patients were analyzed and studied in terms of pathologic complete response (PCR), overall survival (OS) and disease-free survival (DFS).ResultsA total of 283 breast cancer patients were included, 102 (36.04%) with HER2–0 expression and 181 (63.96%) with HER2-low expression, with clinical stage II-III. After the study, the pCR rates of HER2–0 and HER2-low tumors were found to be 19.61% and 11.05%, respectively, which were not statistically different (p=0.071); there were also no significant differences in the pCR rates in both hormone receptor-positive (HR+) and negative (HR-) subgroups of patients. DFS and OS were analyzed for all patients, and there was no statistically significant difference in DFS (p=0.16) and OS (p=0.33) between HER2–0 and HER2-low cases; however, in the HR- subgroup, DFS was worse in HER2-low patients (p=0.027), yet there was no statistically significant difference in OS (p=0.24); in the HR+ subgroup, the HER2 status was not associated with DFS and OS. We also analyzed DFS and OS in PCR and nonPCR patients, and there was no statistically significant difference in DFS (p=0.29) and OS (p=0.54) between HER2–0 and HER2-low cases in PCR patients, and no difference in DFS and OS between HER2–0 and HER2-low cases in nonPCR patients.ConclusionIn breast cancer patients receiving neoadjuvant chemotherapy, no significant differences in chemosensitivity or prognostic outcomes were observed between HER2-low and HER2–0 tumors, considering HR expression subtypes and other current clinicopathological features.